Copyright in the information society : a guide to national implementation of the European directive - Lindner, Brigitte; Shapiro, Ted (Elgar intellectual property law and practice, 2019)
This substantially revised second edition evaluates the Directive on Copyright in the Information Society and its interpretation by the European Court of Justice in the light of its implementation and application in the EU's 28 member states. Following the initial implementation of the Directive, many member states have enacted further legislation to supplement or refine their earlier implementation: this edition will take these important developments into account. Key features of the updated second edition include: ; Chapters authored by experts from all 28 member states, providing detailed analysis on how the Directive has been implemented and applied on a national level ; Contextual chapters on the relevant WIPO treaties and the Directive that highlight areas of discretion left to national legislators ; Updated review of the European Court's case law that serves to interpret the Directive ; Expanded Foreword by Dr Jörg Reinbothe, the architect of the Directive. Combining practical information on implementation of the Directive with the latest academic research this book will be of great value to policy makers, practising lawyers and researchers alike. The book will be of particular interest for the further development of copyright in the Digital Single Market since it captures the status quo of copyright protection in the member states at a decisive moment in the legislative debate.